Islanding detection method of multi‐port photovoltaic DC micro grid based on harmonic impedance measurement. Issue 14 (3rd October 2019) - Ke, Jia; Zhengxuan, Zhu; Qijuan, Zhao; Zhe, Yang; Tianshu, Bi
Abstract : DC Grid does not transmit reactive power, nor does it offer frequency and phase issues. This results in malfunction of conventional islanding detection methods (IDMs) that rely on the above quantities. At present, the DC IDMs proposed in literatures are mostly active power injection methods based on DC/DC converters. However, in a multi‐photovoltaic (PV) DC system, the synchronization of the injection of converters is difficult to guarantee, which may lead to detection failure. This paper proposes an impedance measurement IDM for multi‐PV DC micro grid based on the analysis of high‐frequency impedance model of power electronic devices. The impedance of DC converters is constant at high frequency and the harmonic impedance of the system changes significantly after islanding, so that islanding operation can be accurately detected. The harmonic impedance change directly reflects the structural changes of the system, and its calculation requires less disturbance intensity, which avoids the requirement of synchronous injection. Therefore, the method uses a DC/DC converter for injection, without the need for additional injection equipment. The method has little influence on power quality and theoretically has no none detection zone. Simulation results show that the method can perform accurately islanding detection in multi‐PV DC micro grid.